Ease of Use of Augmented Reality as an Online Learning Tool to Improve Student Performance and Achievement in Wood Carving Art - Ismail; Krishna Pillai, Salini; Iksan, Nur; Abd Arif, Harleny; Panessai, Ismail Yusuf; Abdulbaqie, Azmi Shawkat; Yani, Achmad (Journal of Engineering, Technology, and Applied Science (JETAS), 2021)
Krisis global pasca merebaknya epidemi Covid-19 berdampak pada proses belajar mengajar (PdP). Masalah utama pdP selama epidemi Covid-19 adalah keterbatasan dalam melakukan kegiatan tatap muka di dalam kelas. Oleh karena itu, diperlukan bantuan pembelajaran agar PdP dapat berjalan optimal meskipun tidak ada interaksi tatap muka antara guru dan siswa. Penelitian ini menyoroti penerapan Augmented Reality untuk mendukung pembelajaran jarak jauh dalam situasi epidemi Covid-19, khususnya dalam topik seni ukiran kayu. Aplikasi selular AR Wood Carving Art menggunakan model desain ADDIE. Aplikasi seluler AR Wood Carving Art dievaluasi berdasarkan kegunaannya (ease of use). Berdasarkan hasil penelitian, responden menyetujui bahwa aplikasi selular AR Wood Craving Art berguna dan aplikasi menghemat waktu ketika pengguna menggunakannya sehingga aplikasi selular AR Wood Craving Art efektif digunakan dalam pembelajaran yang membuat pengguna lebih produktif, kreatif, dan inovatif. Ease of Use of Augmented Reality as an Online Learning Tool to Improve Student Performance and Achievement in Wood Carving Art Abstract: The global crisis following the outbreak of the Covid-19 epidemic has had an impact on the teaching and learning process (PdP). The main problem with PdP during the Covid-19 epidemic was the limitation in conducting face-to-face activities in the classroom. Therefore, a learning aid is needed to enable PdP to run optimally even though there is no face-to-face interaction between teachers and students. This research highlights the application of Augmented Reality to support distance learning in the Covid-19 epidemic situation, specializing in Wood Carving Art for the subject of Visual Arts. The AR Wood Carving Art mobile application uses the ADDIE design model. The AR Wood Carving Art mobile application is evaluated based on its ease of use. Based on the result, respondents agree that the AR Wood Craving Art mobile application is useful and the application saves time when users use it, therefore the AR Wood Craving Art mobile application is effectively used in learning which makes users more productive, creative, and innovative. Keywords: Augmented Reality, Ease of Use, Teaching and Learning.